Pre-disaster planning and post-disaster aid: Examining the impact of the great East Japan Earthquake. (March 2017) - Cole, Matthew A.; Elliott, Robert J.R.; Okubo, Toshihiro; Strobl, Eric
Abstract: In this paper we examine the extent to which pre-disaster planning and post-disaster aid can help firms recover from the negative impact of a natural disaster. Using detailed plant-level data covering the areas affected by the March 2011 Great East Japan earthquake and tsunami we find that the number of stopped days of operation was negatively impacted by the disaster although we find that only the tsumani-affected plants experienced reduced sales six months after the earthquake. However, we do find evidence to suggest that post-disaster sales was influenced by a number of pre and post-disaster policies. More specifically, we find that pre-disaster policies such as having alternative transport arrangements and a diversified supplier network positively affect post-disaster sales. We also find that post-disaster aid from local banks and trading partners positively influences post-disaster sales but that direct cash payments from government appears to have no statistically significant effect.